Cognitive functioning and its associated factors among breast cancer patients on chemotherapy at Tikur Anbessa specialized hospital, Addis Ababa Ethiopia: an institution-based comparative cross-sectional study - Edgeit Abebe; Tesfaye Tollesa; Mathewos Assefa; Zelalem Tilahun; Yohannes Dinku; Sofonyas Abebaw; Melkalem Mamuye (BMC Cancer, 2021)
Abstract Background Breast cancer is the second leading cause of cancer in the world. It is the commonest type of cancer in Ethiopia. Cognitive problems are common among breast cancer patients. The study aimed to assess cognitive functioning and its associated factors among breast cancer patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia 2020. Methods Institution-based comparative cross-sectional study was conducted. Study subjects were 117 breast cancer patients on chemotherapy and 117 women without breast cancer who volunteered for the study. Data was collected from May–June 2020. The Mini-mental status exam (MMSE) was used to assess cognitive functioning. Data were entered into Epi Data version 4.6.0.2 and analyzed using STATA version 14 software. Univariable and multivariable linear regression model was fitted to identify factors associated with cognitive functioning. A two-tailed p-value less than 0.05 was used to declare statistical significance. Results Among the total breast cancer patients 41.9% were diagnosed with earlier sage of the diseases (stage I and II), while the rest 58.1% were diagnosed with stage III and stage IV breast cancer. A significant difference in the MMSE score was observed among breast cancer patients and controls (19.76 ± 5.29, 25.18 ± 4.68 p <  0.0001) respectively. In multivariable linear regression analysis being non-breast cancer (Adjusted beta coefficient (Adj.β.coff). = 3.34, 95% CI (1.92–4.76) p <  0.001), hemoglobin gm/dl (Adj.β.coff =0.34, 95% CI (0.04–0.63) p = 0.02), and primary education (Adj.β.coff =2.98 95%CI (1.16–4.96) p = 0.001) secondary level and more education (Adj.β.coff = 5.47, 95%CI (3.51–7.28) p < 0.001) were significantly associated with MMSE cognitive score. Conclusion Breast cancer patients had lower mean MMSE scores when compared to non-breast cancer women. Higher hemoglobin level and higher level of education increase the MMSE cognitive score. Clinicians should incorporate routine screening of cognitive functioning for breast cancer patients and further study is required to evaluate cognitive impairment among breast cancer patients in Ethiopia.